Dynamic nucleotide flipping drives super-resolution fluorescence activation in the RhoBAST RNA aptamer - Tai, Xiaoqing; He, Mengqi; Mitteregger, Christoph; You, Huiqin; Xiong, Peng; Hu, Zejia; Bao, Xinyue; Shen, Xin; Li, Hongcheng; Li, Yu; Zhang, Jinzhu; Micura, Ronald; et al. (浪淘沙预印本平台, 2026)
Super-resolution imaging with RhoBAST fluorogenic RNA aptamer sheds new light on decoding RNA dynamics with high spatiotemporal resolution. To uncover the molecular basis underlying its exceptional photophysical properites, we determined the first free-form structure of RhoBAST, along with its ligand-bound complexes with TMR-DN and related analogs. RhoBAST adopts an inverted ’V’-shaped architecture, with the fluorophore accommodated between the J2/3 and L3 loops. Comparative structural analyses reveal that nucleotide G38 undergoes a pronounced conformational transition—from an inward-facing to an outward-flipped orientation—upon ligand binding. Structure-guided mutagenesis and complementary biophysical assays, including fluorescence spectroscopy, surface plasmon resonance, and 2-aminopurine kinetics, establish that this dynamic nucleotide flipping facilitates rapid ligand turnover and fluorescence flickering, the hallmark of super-resolution imaging. These findings uncover a previously unrecognized nucleotide-flipping mechanism in a fluorogenic RNA aptamer, providing a structural and mechanistic blueprint for the rational design of next-generation super-resolution RNA imaging tools.